COVID-19 control: can germany learn from China? - Müller, Olaf; Jahn, Albrecht (International journal of health policy and management, 2020)
The coronavirus disease 2019 (COVID-19) outbreak started in China in December 2019 and has developed into a pandemic. Using mandatory large-scale public health interventions including a lockdown with locally varying intensity and duration, China has been successful in controlling the epidemic at an early stage. The epicentre of the pandemic has since shifted to Europe and The Americas. In certain cities and regions, health systems became overwhelmed by high numbers of cases and deaths, whereas other regions continue to experience low incidence rates. Still, lockdowns were usually implemented country-wide, albeit with differing intensities between countries. Compared to its neighbours, Germany has managed to keep the epidemic relatively well under control, in spite of a lockdown that was only partial. In analogy to many countries at a similar stage, Germany is now under increasing pressure to further relax lockdown measures to limit economic and psychosocial costs. However, if this is done too rapidly, Germany risks facing tens of thousands more severe cases of COVID-19 and deaths in the coming months. Hence, it could again follow China’s example and relax measures according to local incidence, based on intensive testing.
Gesehen am 04.11.2020